Resources needed for US CDC's support to the response to post-epidemic clusters of Ebola in West Africa, 2016 - Cristina Carias; Bishwa B. Adhikari; Fatima Ravat; Martin I. Meltzer; Barbara J. Marston (BMC, 2018)
Abstract Background West African countries Liberia, Sierra Leone, and Guinea experienced the largest and longest epidemic of Ebola virus disease from 2014 to 2016; after the epidemic was declared to be over, Liberia, Guinea, and Sierra Leone still experienced Ebola cases/clusters. The United States Centers for Disease Control and Prevention (US CDC) participated in the response efforts to the latter Ebola clusters, by assisting with case investigation, contact identification, and monitoring. This study aims to estimate the cost to the US CDC of responding to three different Ebola clusters after the end of the Ebola epidemic in 2015: i) Sierra Leone, Tonkolili (Jan 2016, 2 Ebola cases, 5 affected regions); ii) Guinea, Nzerekore (Mar-May 2016, 10 Ebola cases, 2 affected regions); iii) Liberia, Somali Drive (Mar 2016, 3 Ebola cases, 1 affected region). Main text After interviewing team members that had participated in the response, we estimated total costs (expressed in 2016 US Dollars [USD]), where total costs correspond to travel costs, deployed personnel costs, costs to prepare for deployment, procurement and interagency collaboration costs, among others. We also estimated cost per cluster case (corresponding to the total costs divided by the total number of cluster cases); and cost per case-affected-region (equal to the total costs divided by the product of the number of cases times the number of regions affected). We found that the response cost varied sixteenfold between USD 113 166 in Liberia and USD 1 764 271 in Guinea, where the main cost drivers were travel and personnel costs. The cost per cluster case varied tenfold between 37 722 in Liberia (three cases) and USD 347 226 in Sierra Leone, and the cost per case-affected-region varied threefold between USD 37 722 in Liberia and USD 88 214 in Guinea. Conclusions Costs vary with the characteristics of each cluster, with those spanning more regions and cases requiring more resources for case investigation and contact identification and monitoring. These data will assist policy makers plan for similar post-epidemic responses.